2015
DOI: 10.1111/bcp.12582
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic model of free and total ropivacaine after transversus abdominis plane nerve block in patients undergoing liver resection

Abstract: AIMSThe aim of this study was to develop a pharmacokinetic model in order to characterize the free and total ropivacaine concentrations after transversus abdominis plane block in a population of patients undergoing liver resection surgery. In particular, we evaluated the impact of the size of liver resection on ropivacaine pharmacokinetics. METHODSThis work is based on a single-centre, double-blinded, randomized, placebocontrolled study. Among the 39 patients included, 19 patients were randomized to the ropiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In different pharmacokinetic studies, the unbound fraction of ropivacaine varies widely, the 2 main reasons being differences in analytical methods and differences in α1-acid glycoprotein. 21 Because we used the same analytical method and ultrafiltration technique in both studies and differences in α1-acid glycoprotein between the 2 study populations seem unlikely, we have no explanation for this difference in the unbound fraction of ropivacaine.…”
Section: Discussionmentioning
confidence: 95%
“…In different pharmacokinetic studies, the unbound fraction of ropivacaine varies widely, the 2 main reasons being differences in analytical methods and differences in α1-acid glycoprotein. 21 Because we used the same analytical method and ultrafiltration technique in both studies and differences in α1-acid glycoprotein between the 2 study populations seem unlikely, we have no explanation for this difference in the unbound fraction of ropivacaine.…”
Section: Discussionmentioning
confidence: 95%
“…Ropivacaine is predominantly eliminated by extensive metabolism in the liver, which depends on hepatic blood flow as well as the degree of protein binding. Edouard et al [ 32 ] reported that the resection of three or more liver segments was associated with a 53% decrease in the free ropivacaine clearance. Therefore, the first limitation was that we did not measure plasma ropivacaine concentrations in group T perioperatively, although none of the patients had symptoms of local anesthetic systemic toxicity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important pharmacological characteristics of ropivacaine is that high systemic exposure to it often results in central nervous system disorders and cardiovascular disorders. 9 In a study including individuals receiving titrated intravenous infusions of ropivacaine, it was indicated that the onset of neurological symptoms occurred at a mean total plasma ropivacaine concentration of 2.20 μg/mL and free ropivacaine concentration of 0.15 (0.08) μg/mL. 10 In previous studies, potentially toxic plasma concentrations of ropivacaine have been assessed after ultrasoundguided CL-TAP blocks for cesarean sections and open major gynecological surgery.…”
Section: Safety Of Bd-tap Block With Ropivacaine In Laparoscopic Hepamentioning
confidence: 99%